Changes in CD45 isoform expression accompany antigen-induced murine T-cell activation. - Birkeland, M L (1989)
Leukocytes express a family of plasma membrane proteins called CD45 or the leukocyte common antigen. Isoforms of various molecular masses, 180-240 kDa, are produced by alternative splicing and usage of three exons, named A, B, and C, that encode the N-terminal portion of the external domain. By using monoclonal antibodies that precipitate B exon-dependent and B exon-independent isoforms we find that both murine CD4+ and murine CD8+ T cells selectively down-regulate the B exon-dependent forms of CD45 during an immune response. This change was monitored by using fluorescence-activated cell sorter (FACS) analysis and immunoprecipitation from surface radioiodinated and metabolically labeled cells. The loss of the 190-kDa B exon-dependent isoform during T-cell activation is accompanied by an increased production of a 180-kDa form, which does not contain the B exon-encoded sequence. This accounts for our observation that the overall expression of CD45, as assessed by FACS analysis, does not change.